2013
DOI: 10.9790/2402-0451829
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Serum Creatine Phosphokinase and Severity of Acute Organophosphorus Poisoning: A Prospective Clinical Study (2012-2013

Abstract: Organophosphorus (OP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
7
11
0
Order By: Relevance
“…Most patients were from rural area (65%) with 46% patient living below poverty line. These findings were similar to studies conducted by Bhattacharya et al, 14 Sen R et al 22 and Reddi et al 23 Most common mode was suicidal (88%) and most common occupation was student (30%) followed by farmer (22%) which is similar to studies conducted by Dubey et al, 21 Nermeen et al 20 Chlorpyrifos (28%) was most common compound ( Figure 1) involved followed by Phorate (23%) which is commonly used pesticide in our area. However similar trend was noted in study of Bhattacharya et al 14 and Nagarajan et al 24 Vomiting (86%), salivation (71%) were most common symptoms ( Figure 2) while miosis (88%), bradycardia (62%) were most common sign (Figure 2) similar to study of Agrawal S et al 19 Creatine Phosphokinase, an enzyme which is expected to rise in patients with OP compound poisoning due to muscle necrosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most patients were from rural area (65%) with 46% patient living below poverty line. These findings were similar to studies conducted by Bhattacharya et al, 14 Sen R et al 22 and Reddi et al 23 Most common mode was suicidal (88%) and most common occupation was student (30%) followed by farmer (22%) which is similar to studies conducted by Dubey et al, 21 Nermeen et al 20 Chlorpyrifos (28%) was most common compound ( Figure 1) involved followed by Phorate (23%) which is commonly used pesticide in our area. However similar trend was noted in study of Bhattacharya et al 14 and Nagarajan et al 24 Vomiting (86%), salivation (71%) were most common symptoms ( Figure 2) while miosis (88%), bradycardia (62%) were most common sign (Figure 2) similar to study of Agrawal S et al 19 Creatine Phosphokinase, an enzyme which is expected to rise in patients with OP compound poisoning due to muscle necrosis.…”
Section: Discussionsupporting
confidence: 89%
“…18 Estimation of CPK is economical and levels are increased both in acute as well as in intermediate syndrome and can be used as a low budget, easily available prognostic marker for acute organophosphorus poisoning. 14,19,20 Aims and Objectives…”
Section: Introductionmentioning
confidence: 99%
“…Majority of the patients in our study were females which accounting for 51.3% 41 cases and males were 39 cases 48.8%. This is consistent with Murat S et al [11] study with female predominance and also in the study done by Hassan NAM et al [10] with 51.7% were males and 48.3% were males. But in Bhattacharyya et al [8] study 66.6% were males and 33.3% were females.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the study done by Bhattacharyya et al [8] which showed that most commonest age group is 21-30 years and also in Mcihammet G et al [9]. But in the study done by Hassan NAM et al [10] the common age group is 11-20 years. As we can see the most common group of affected individuals are among youngsters and the reason may be because these individuals are vulnerable to various emotion conflicts that occur during this phase of life.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation